Endothelial Nitric Oxide Synthase Gene T-786C Polymorphism in Renal Transplant Recipients - N Azarpira; H Karimi; M Ayatolahi; M Aghdai; H Salahi; SA Malek-Hosseini; J Roozbeh; M Sagheb; GA Raisjalali; A Behzadi; R Yaghobi; A Bahador; et al. (International Journal of Organ Transplantation Medicine, 2011)
Background: Nitric oxide (NO) is a major mediator in vascular biology, regulating regional blood flow. NOand the enzymes required for its production contribute to ischemia-reperfusion injury. The T-786C functionalpolymorphism in the promoter region substantially reduces promoter activity of the endothelialnitric oxide synthase (eNOS) gene and compromises endothelial NO synthesis.Objective: To examine the association between T-786C (rs 2070744) single nucleotide polymorphism(SNP) in eNOS gene and the development of acute rejection in renal transplant patients.Methods: 60 renal transplant recipients (30 with episodes of acute rejection (ARs) and 30 without rejection(non-ARs)), between June 2008 and March 2010, were included in this study. The polymorphism wasdetermined by PCR-restriction fragment-length polymorphism analysis.Results: The distribution of the genotypes were TT/TC/CC 60%, 33.4%, 6.6%, and 43%, 46.7%, 13.3% inARs and non-ARs, respectively (p=0.28). The frequency of T-allele was 76.7% and 66.3%; and for C-allelewas 66.6% and 33.3% in ARs and non-ARs, respectively (p=0.09). There were no significant associationsbetween these polymorphisms and acute and chronic kidney allograft rejection.Conclusion: We could not detect any significant association between polymorphism in T-786C of eNOS geneand the development of acute rejection.